The Latin American Drug Trade - Chalk, Peter (RAND Corporation, 2023)
Transnational crime remains a particularly serious problem in Latin America, with most issues connected to the drug trade. There are several relevant roles that the U.S. Air Force can and should play in boosting Mexico's capacity to counter drug production and trafficking, as well as further honing and adjusting its wider counternarcotics effort in Latin America.